Pengenalan Bendera Negara Dengan Fisher Yates- Shuffle Pada Game Edukasi Android Menggunakan Metode GDLC - Desty Rahma Fadilla; Fauziah Fauziah; Rima Tamara Aldisa (Journal of Information System Research (JOSH), 2023)
This research aims to address the negative impact of less educational games by creating an interactive educational game for Android that combines learning about national flags and memorizing flag images, thus enhancing logical thinking skills in children. It is developed using the Flutter framework as the development platform and follows the GDLC method, with alpha testing conducted using the blackbox method. The Fisher-Yates Shuffle algorithm is implemented for shuffling the flag images and the order of elements in the card list. The testing method involves using the Debug Console in Visual Studio Code to verify the success of the shuffling process. The conducted testing, performed six times, demonstrates the algorithm's success in shuffling the card order for each level. In the easy level, the randomized order is 6, 10, 8, 5, 3, 4, 11, 2, 7, 1, 12, 9. In the normal level, the randomized order is 6, 11, 20, 16, 1, 13, 19, 17, 9, 2, 15, 4, 10, 12, 14, 8, 5, 7, 2, 18. In the hard level, the randomized order is 2, 14, 1, 21, 7, 18, 24, 22, 10, 23, 6, 11, 15, 9, 17, 4, 8, 3, 5, 13, 16, 12, 19, 20. The Fisher-Yates Shuffle algorithm successfully generates diverse shuffling of flag images and avoids repeating the random order of cards each time the game starts. Thus, this game can provide stimulation to the brain and encourage children to effectively enhance their object memory skills.